The role of trade openness for industrial sector development: panel data evidence from SAARC region. Issue 1 (4th January 2016) - Tahir, Muhammad; Ruiz Estrada, Mario; Khan, Imran; Afridi, Muhammad Asim
Abstract : Purpose: – The purpose of this study is to focus on South Asian Association for Regional Cooperation (SAARC) member economies to examine the impact of trade openness on the industrial sector development. Design/methodology/approach: – Panel data econometric techniques are used to the data for the period 1980-2013 for the selected six countries, namely, Bangladesh, Bhutan, India, Nepal, Pakistan and Sri Lanka. Findings: – It is found that trade openness has positively and significantly influenced the industrial sector of the sampled countries. Other determinants such as education and investment have also played a key role in helping the selected developing countries to develop their industrial sectors. Practical implications: – The study suggests the policy-makers of the SAARC member countries to liberalize international trade substantially to enhance the contributions of industrial sector toward gross domestic product (GDP) and to achieve the dreamed goal of sustainable long-run growth for the region. Originality/value: – An explicit relationship between trade openness and industrial sector of the SAARC member economies is yet to be examined.